Hyperprogressive disease in non-small cell lung cancer after PD-1/PD-L1 inhibitors immunotherapy: underlying killer - Li, Yanping; Chen, Tianhong; Nie, Tian Yi; Han, Juyuan; He, Yunyan; Tang, Xingxing; Zhang, Li (Frontiers in Immunology, 2023)
Immune checkpoint inhibitors (ICIs) target the negative regulatory pathway of T cells and effectively reactive the anti-tumor immune function of T cells by blocking the key pathway of the immune escape mechanism of the tumor—PD-1/PD-L1, and fundamentally changing the prospect of immunotherapy for non-small cell lung cancer patients. However, such promising immunotherapy is overshadowed by Hyperprogressive Disease, a response pattern associated with unwanted accelerated tumor growth and characterized by poor prognosis in a fraction of treated patients. This review comprehensively provides an overview of Hyperprogressive Disease in immune checkpoint inhibitor-based immunotherapy for non-small cell lung cancer including its definition, biomarkers, mechanisms, and treatment. A better understanding of the black side of immune checkpoint inhibitors therapy will provide a more profound insight into the pros and cons of immunotherapy.